ASSESSMENT OF WATER RESOURCES OF THE BOLSHOY KINEL RIVER FOR SUSTAINABLE WATER SUPPLY - Aleksandra V. Selezneva; Ksenia V. Bespalova (Водное хозяйство России: проблемы, технологии, управление)
The article presents the results of analysis of the water flow data for main rivers in the Bolshoy Kinel River basin from the moment of the instrumental observation start in 1993. Analysis of inter/annual runoff of the Bol Kinel River showed that the average flow rate was 37.7 m3/s, the largest – 72.6 m3/s (1991), the smallest – 8.54 m3/s (1935). Starting from the 60s of the last century, the years 1991, 1987, 1990, and the low-water years were 1967, 1975, and 1984. Due to climatic changes, the annual flow of the river for the period 1933-2010 increased from 34.6 m3/s to 37.5 m3/s. At the same time, the runoff of spring flood increased and the low-water runoff decreased. Analysis of seasonal runoff variability showed that the minimum runoff during the low-water period is a limiting factor for water supply. The smallest minimum monthly flow rate was 3.14 m3/s (January 1939). The lowest daily water flow rate was 0.71 m3/s (September 3.4, 1940). The results obtained prove that the Bol Kinel River during the low-water period of extremely dry years is an unreliable source of water supply. To ensure sustainable water supply in conditions of low water amid global climate warming, it is necessary to develop additional reserve options for supplying water to the urban population.